BUILD ECOSYSTEM: LEADERSHIP STRATEGY IN SANGGAR ANAK ALAM (SALAM) NON-FORMAL SCHOOL IN BANTUL DISTRICT OF YOGAYAKARTA, AS AN EFFORT TO MAINTAIN ITS EXISTENCE - Zahra Fadhilah Putri (Khazanah Intelektual, 2020)
Along with the emergence of problems in formal education, such as: inflexible time and teaching and learning process, gave rise to a new innovation of non-formal education programs. However, non-formal education often faces problems in increasing its existence. therefore, this study aims to explore leadership strategies in increasing the existence of non-formal schools. This research was conducted at Sanggar Anak Alam (SALAM) with qualitative methods, and collecting techniques through interviews and observations. SALAM has a significant development, proven by getting an award from America in 1991. It also has several strategies to increase its existence, including: conducting regular parent gatherings, conducting discussions, holding legion and public market programs, and making books.